Serikat Pekerja Indonesia dalam Memperjuangkan Upah Layak dan Perlindungan dari PHK Massal: Studi Kasus PT Sri Rejeki Isman Tbk (Sritex) - Bintang Salma Nafilah; Rieka Aditia Pratiwi; Siska Ayu Wulandari; Putri Agnessia Pramudita; Tifia Merry Imtyas; Aldi Mufid Faiza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Trade unions have an important role in protecting workers' rights, especially in fighting for decent wages and protection against mass layoffs. This study examines the role of trade unions in Indonesia in efforts to improve the welfare of their members through a case study at PT Sri Rejeki Isman Tbk (Sritex), where Sritex is the largest textile company in Indonesia that experienced a mass layoff case. This paper explains the various roles of trade unions in negotiations with companies and the challenges faced by trade unions such as company financial pressure, weak bargaining position in the negotiation process and limited worker participation in company decision-making. This paper also emphasizes the importance of increasing the capacity of trade unions such as through member training programs and strengthening advocacy strategies. In addition, building effective social communication between trade unions, management and the government in order to realize sustainable industrial relations amidst the challenges of the globalization era.